Monitoring of five biogenic amines and microbiologic profile in fish matrices in different storage conditions - Pereira, Inês (2019)
Biogenic amines are low molecular weight nitrogen compounds that result from the action of microbial metabolism from free amino acids, mainly produced by Enterobactereaceae, during spoilage and fermentation of fish and fish products. The presence of biogenic amines in foodstuffs may lead to intolerance or food poisoning, especially due to the consumption of high concentrations of histamine. The action of histamine can be potentiated by the presence of other biogenic amines, such as putrescine and cadaverine, considered the most reliable indicators of fresh fish quality. The purpose of this study was to detect and quantify in simultaneous five biogenic amines, histamine, tryptamine, tiramine, cadaverine and putrescine, by ultra performance liquid chromatography (UPLC®) coupled with a Photodiode Array (PAD) detector, using the AccQ Fluor reagent from Waters (AccQ-TagTMUtltra kit), as derivating agent. The analytical assays, were performed in two food samples tuna and shrimp purchased on the market during their shelf-life. These products were analyzed after storage at 4 ± 1ºC during 48h, 72h, 120h and 240h. At the same time, microbiological quantification was performed to establish a correlation between the level (cfu/g) of biogenic amine-producing bacteria present and the concentration (mg/Kg) of biogenic amines produced. The results obtained showed that between 48h to 240h, the level of microorganisms increased (2 log10 cfu/g) and the bacteria detected such as Enterobacteriaceae, Vibrio, Pseudomonas and Aeromonas, as well as increased histamine concentrations (43,5 mg/Kg - > 200 mg/Kg), failing the regulated histamine level, are in accordance with the described in the scientific literature. This study indicates that the concentration of biogenic amines is affected by the growth of biogenic amine producers under the influence of temperature and time, fundamental contributory factors for the microbiological quality and safety of fish and fish products.